FACTORS AFFECTING THE EFFICIENCY OF REAL SECTOR ENTERPRISES IN UZBEKISTAN - Dilshodbekov Jawakhir,; Anafiyaev Abdurashid Mamasidikovich, (Ustozlar uchun, 2025)
The article is devoted to the analysis of factors affecting the efficiency of enterprises in the real sector of the economy of Uzbekistan. The author examines the internal and external conditions that determine the competitiveness of companies, their resilience to global challenges and the ability to integrate into international production chains. Particular attention is paid to the impact of the technological level of production, management efficiency, quality of human capital, financial management and logistics on the operating activities of enterprises. Key aspects of public policy, regulation of the tax system and investment climate that affect the development of the real sector are considered.